Northward movement of the tropical dinoflagellate Ornithocercus and Triposolenia genera in Korean coastal waters is strongly associated with the inflow of the Jeju Warm Current - Lee, Bora; Kim, Jong Kyu; Kim, Miran; Choi, Byoung-Ju; Kim, Kwang Young; Park, Myung Gil (Frontiers in Marine Science, 2023)
Rising seawater temperatures are causing geographic shifts in the composition and abundance of the marine plankton that make up the microbial food web. Over the past few years, the water temperature around the Korea Strait has been increasing rapidly. Twelve cruise surveys were conducted in the Jeju Strait between 2017 and 2019 to monitor the presence of the tropical dinoflagellate genera Ornithocercus and Triposolenia, which are brought in by the Jeju Warm Current. Additionally, passive tracer experiments were performed using the Regional Ocean Modeling System to understand how the warm currents impact the Jeju Strait. The results of these simulations were then compared against the distribution ranges and abundance of Ornithocercus and Triposolenia. The study found that there were significant seasonal variations in abundance and spatial distribution of the tropical dinoflagellates during the sampling period, particularly during September and November when they were highly abundant and widely distributed. These patterns were closely related to the intensity and path of the Jeju Warm Current, particularly from southeastern offshore (EKB02; Eastern Kuroshio Branch02) rather than from southwestern offshore (EKB01; Eastern Kuroshio Branch01) of Jeju Island. The study also found no tropical dinoflagellates at any of the stations near the south coast of Korea during the sampling period. These findings suggest that the Ornithocercus and Triposolenia tropical dinoflagellate genera may serve as useful biological indicators to monitor the advection of warm currents into the Jeju Strait, Korea.